A near-infrared light-mediated antimicrobial based on Ag/Ti3C2Tx for effective synergetic antibacterial applications. Issue 37 (16th September 2020) - Zhu, Xiaoquan; Zhu, Yingnan; Jia, Ke; Abraha, Bahreselam Sielu; Li, Yang; Peng, Wenchao; Zhang, Fengbao; Fan, Xiaobin; Zhang, Lei
Abstract : The antimicrobial effect of Ag/Ti3 C2 T x could be significantly strengthened upon near-infrared light exposure. Abstract : Designing antimicrobials with high efficiency and long-term antibacterial activity is an imperative issue. We found that the antimicrobial effect of Ti3 C2 T x and Ag/Ti3 C2 T x could be significantly strengthened upon near-infrared light exposure. The synergistic antibacterial mode of the photothermal bactericidal effect and intrinsic bacterial activity have been revealed, which confirms that the Ti3 C2 T x MXene is an excellent near-infrared light-mediated nanoplatform for antibacterial applications. To further test the antibacterial effect in practical applications, Ag/Ti3 C2 T x embedded hydrogels were used as wound dressings in a wound model experiment. They exhibit outstanding bacterial inhibition and wound healing performance with near-infrared light exposure. This work inspires us to explore the MXene-based photothermal platform in terms of antibacterial application.